Integrated solid waste management for local governments a practical guide. (Pacific economic monitor., 2017)
This practical reference guide introduces key concepts of integrated solid waste management and identifies crosscutting issues in the sector, derived mainly from field experience in the technical assistance project Mainstreaming Integrated Solid Waste Management in Asia. This guide contains over 40 practice briefs covering solid waste management planning, waste categories, waste containers and collection, waste processing and diversion, landfill development, landfill operations, and contract issues.